IN VITRO STUDY OF AN AQUEOUS EXTRACT OF ECLIPTA ALBA HASSK. FOR HEPG2 CELL LINE - Kulkarni Dhananjay Vyanktesh,; Tathe Mangal Suresh,; Harke Sanjay Ningappa, (International Journal of Ayurveda and Pharma Research, 2020)
It is the need of the day to identify the new anticancer herbal drug, which not only in possession of good anticancer effects but also cost effective. Here we are presenting such an anticancer Ayurvedic herb which is used since the centuries for the treatment of different diseases of diverse origin. Eclipta alba Hassk., also called as Bhringraj is very important medicinal herb in many medicinal formulations. Though it is commonly used for hair growth, many evidences found its hepatoprotective activity.Here we are presenting all aspects about Bhringraj in terms of qualitative and quantitative values and we have also tried to prove the anticancer activity of it for hepatic cancer. We have used the aqueous extract of Eclipta alba Hassk. for phytochemical analysis, TLC, HPLC analysis to test active chemical components in it. Extract showed presence of many active chemical components which were responsible for its anticancer activity. In vitro study we used the aqueous extract of Eclipta alba Hassk. for the evaluation of its effects on HepG2 (Human liver cancer cell line). The SRB assay results were used to evaluate the anti-cancer activity of the extract. The effects of whole plant extract on cancer cell line were studied. Percentage of cell growth and cell viability were calculated from tabulated result values of srb assay. The experiment revealed that the average percentage of growth inhibition was 68.74%. Cell viability SRB assay also showed significant growth inhibition, at the same time statistical analysis of SRB assay also proved significant results. The research performed here is very useful for set up of different extract studies of Bhringraj for its anticancer activity.